AUDIT INTERNAL DALAM PENGELOLAAN MUTU PENDIDIKAN DI SMK MUHAMMADIYAH 1 KLATEN - Suyatmi, Suyatmi (2011)
Research purpose is describing internal audit character in education quality management of SMK Muhammadiyah 1 Klaten. Specific purposes of this research are: (1) describing internal audit instrument character by Internal Audit Team in education quality management of SMK Muhammadiyah 1 Klaten. (2) knowing auditor activity character by Internal Audit Team in education quality management of SMK Muhammadiyah 1 Klaten. (3) knowing auditor work relation to auditee in education quality management of SMK Muhammadiyah 1 Klaten. This research is qualitative research. Research location is in SMK Muhammadiyah 1 Klaten. Collecting data technique uses depth interview, observation, documentation. Data analysis uses managed matrix qualitative. Research results are (1) internal audit instrument is one of internal audit team work document in education quality management of SMK Muhammadiyah 1 Klaten as supporting tools of audit execution effectiveness and efficiency and as tool to record result/ audit finding. Internal instrument includes checklist and form to write finding report. Internal audit team orients on job description, to know other internal audit team performanceaccording to Procedure and Operational Standard (SOP). (2) auditor activity includes preparation activity, execution and reporting. Internal audit preparation by internal auditor team in SMK Muhammadiyah 1 Klaten, is one of obligation requirement for ISO 9001 : 2008 systematic organization. Auditor has responsibility to make checklist audit, explain audit requirement to auditee, document audit finding, and report audit result to audit lead. (3) auditor and auditee is quality management setting which collaborate in improving education quality. They have collaborative work relation to get information and give information about audited object. Auditor and auditee collaboration in internal audit preparation is internal audit requirement explanation to auditee, while auditee prepares all needs in internal audit activity. Auditee teamwork shown in information giving about audited object, auditor guiding while audit execution, supplying supporting data for auditor and supplying evidence for auditor